Reactualisation of the Pretrial Role in Guaranteeing a Fair Trial in Indonesia: Lessons from the Pegi Setiawan Case - David, Nathanael Gabriel; Fatimah, Fines; Birham, Rizki Emil (Kertha Patrika, 2025)
Constitutional Court Decision Number 21/PUU-XII/2014 has become an important milestone in expanding the scope of pretrial proceedings in Indonesia. The ruling confirms that the designation of suspects, searches, and seizures can be challenged through pretrial mechanisms, even though this norm was not explicitly stated in Article 77(a) of Law No. 8 of 1981 on Criminal Procedure (KUHAP). Interestingly, in judicial practice, Decision Number 10/Pid.Pra/2024/PN Bdg in the case of Pegi Setiawan actually used the Constitutional Court's legal considerations, not just the verdict, as the basis for the sole judge's argument. This reveals a shift in methodology in the use of Constitutional Court decisions by first instance judges. This article examines the position of legal considerations in Constitutional Court Decision Number 21/PUU-XII/2014, including dissenting opinions and concurring opinions, as well as their implications for pretrial practice. This research is a type of normative juridical research with a legal material collection technique using a document study or literature research method. This analysis is also directed at the need to reformulate pretrial norms in Indonesian criminal procedure law in the future so that they are in line with the principles of legal certainty, protection of human rights, and the principle of due process of law.
Keywords: Criminal Procedure; Constitutional Court; Indonesia; Pre-trial; Suspects